2016
DOI: 10.1051/e3sconf/20160914023
|View full text |Cite
|
Sign up to set email alerts
|

Creep response in shear of clayey geo-materials under saturated and unsaturated conditions

Abstract: Abstract. Translational slides in clays are often characterized by long-lasting intermittent movements associated with the fluctuations of pore-water pressure. Physically-based models designed to support hazard analysis of landslide movements and early warning systems require the integration of time-dependent (viscous) constitutive models for the shear displacements because landslide movements are typically controlled by the viscous behaviour of the clay geomaterial. This paper presents an investigation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Submitted Nov 2018; Published Oct 2019. https://doi.org/10.1061/(ASCE) GM.1943-5622.0001507. magnitude of reconstituted clays from the sliding zone soils of the Qianjiangping landslide in triaxial conditions and reported a decrease in creep strains with an increase in soil suction. Nazer and Tarantino (2016) investigated the viscous response (in both creep and relaxation modes) during shearing of reconstituted Ball clay using shear box and developed an analogue model for simultaneous modelling of creep and relaxation. Wang et al (2017) performed a set of triaxial stress-relaxation tests on unsaturated lime-treated expansive clays of Hefei Xianqiao Airport site in China, at suctions of 50 and 100 kPa, and studied the effects of pre-relaxation strain level, pre-relaxation strain-rate, and relaxation time.…”
Section: Introductionmentioning
confidence: 99%
“…Submitted Nov 2018; Published Oct 2019. https://doi.org/10.1061/(ASCE) GM.1943-5622.0001507. magnitude of reconstituted clays from the sliding zone soils of the Qianjiangping landslide in triaxial conditions and reported a decrease in creep strains with an increase in soil suction. Nazer and Tarantino (2016) investigated the viscous response (in both creep and relaxation modes) during shearing of reconstituted Ball clay using shear box and developed an analogue model for simultaneous modelling of creep and relaxation. Wang et al (2017) performed a set of triaxial stress-relaxation tests on unsaturated lime-treated expansive clays of Hefei Xianqiao Airport site in China, at suctions of 50 and 100 kPa, and studied the effects of pre-relaxation strain level, pre-relaxation strain-rate, and relaxation time.…”
Section: Introductionmentioning
confidence: 99%
“…Lai et al (2014) [4] measured volume change using unsaturated triaxial compression apparatus, which controlling matric suction cause deformation, and was possible to predict the slope stability. As similar unsaturated soil researches, Nazer and Tarantino (2016) [5] conducted out unsaturated soil creep test in order to investigate deformation behaviour associated with suction considering. The coverage literature is effectively to solve the hydration-mechanical properties for bentonite material.…”
Section: Deformation Due To Suction Changingmentioning
confidence: 99%
“…Tang et al conducted an in situ triaxial test, believing that the sliding zone soil of the Huangtupo landslide was part of a creep process, and derived a constitutive equation with linear and nonlinear viscoplastic terms to fit the creep process of the sliding zone soil [2]. At present, the direct shear creep test of sliding zone soil is mostly focused on the creep damage stage but not on the attenuation creep stage of sliding zone soil [12,13]. Through direct shear tests, Zhu et al found that the red-bed sliding zone soil was in the accelerated creep stage and proposed the long-term strength of the sliding zone soil [14].…”
Section: Introductionmentioning
confidence: 99%